Peningkatan Kemampuan Membaca Al Quran Bagi Ibu-Ibu Pengajian Nurul Jannah Surabaya - Muzamil, Muzamil (Proceedings of Annual Conference on Community Engagement, 2018)
Abstract: Reading Qur’an properly required fo every Muslims and make reciting Qur’anic verses regularly accustomed. But in fact, not all of them have such ability. This can be observed in mothers or housewives of Nurul Jannah Islamic group, staying in Sidotopo Wetan, Kenjeran, Surabaya. Some of them indeed had ability in reading Qur’an in their adolescent times, but when they are becoming mothers or housewives, the ability is not regularly used, even not all. To overcome this problem, after an observation and deep interview with some of housewives and mothers in that Islamic group of mothers, we and some of them established a additional religious meeting for mothers and/or housewives as a coordinating institution accommodating activities in rebuilding and improving ability in reading Qur’an among mothers and housewives in that islamic group of mothers. Activities in the meeting is focused in reciting Qur’an basicly, and it is well kept in an unwearied combination of some activities intended to the members of the meeting.